Experimental and analytical study of the elliptical vibration-assisted turning process with the dynamic friction model. (June 2014) - Nosouhi, Reza; Behbahani, Saeed; Amini, Saeed; Khosrojerdi, Mohammadreza
A novel analytical model for prediction of forces in elliptical vibration-assisted turning using a dynamic friction model is presented in this article and verified with experimental elliptical vibration-assisted turning tests. In elliptical vibration-assisted turning process, the main cause of force reduction is the reversal of the friction force direction in a fraction of vibration cycle time. In analytical modeling of elliptical vibration-assisted turning, the change of the relative sliding velocity direction causes a stick–slip condition which cannot be detected with static friction models like Coulomb model. In this research, a dynamic friction model, named LuGre model, is used to predict the machining forces in elliptical vibration-assisted turning. To derive the model coefficients, a series of orthogonal cutting experiments are performed on Al 6061, Al 7075 T6, Copper and Inconel 718, and the friction coefficients are identified using genetic algorithm optimization method. The cutting forces are determined by incorporating the friction forces calculated from LuGre model. To verify the results, a series of elliptical vibration-assisted turning experiments are performed on four above-mentioned workpiece materials using an elliptical vibration-assisted turning tool. The machining forces are then compared with the analytical results. The results achieved from the analytical solution using LuGre dynamic friction model are in a good agreement with experimental results.